Specific Features of Mental Health of Law Enforcement Officers – Participants of the Anti-Terrorist Operation (Law and Safety, 2019)
The practice of conduct of operations has proven that not every participant in these events endures painlessly the extreme conditions of the battle for their mental health. Under the intense influence of psycho-traumatic factors of the combat environment, a law enforcement officer can get mental disorders of various degree of severity, which lead to a partial or complete loss of combat capability.The author has provided results of studying mental health of law enforcement officers – participants in the anti-terrorist operation after a month of their last business trip. Mentally healthy law enforcement officers had high stress, depletion of internal resources, the formation of an accentuation of personality and symptoms of emotional burnout with a reduction in professional duties, which can lead to emotional problems (anxiety, affective fluctuations, decreased productivity). This category of law enforcement officers requires the conduction of psycho-correctional measures.Law enforcement officers with moderate degree of post-traumatic disorder have increased affective instability, flatness and conservatism; psychosomatic and vegetative disorders have emerged, indicating the need for psychological assistance to these individuals, despite the absence of clear PTSD clinical criteria.Law enforcement officers, who received psychological assistance in connection with clear features of post-traumatic disorder, on the background of significant reduction of psycho-pathological symptoms, there is tendency to socially approved behaviors, while emotional limitation – “insensitivity”, is formed, which is evidenced for the need to conduct psychological rehabilitation with them.It has been substantiated that, regardless the degree of psychological trauma, at different stages of psychological support of the professional activities of law enforcement officers, it is necessary to carry out psycho-correctional measures.
Keywords: psychological trauma; law enforcement officer; borderline mental disorders; stress factors; mental health; anti-terrorist operation; PTSD